Estimation of shear wave velocity using 1-D Multichannel Analysis of Surface Waves (MASW) and shear modulus of peat - Basri, Kasbi; Zainorabidin, Adnan; Mohd Masirin, Mohd Idrus; Mohd Said, Mohd Jazlan; Abdurahman, Mohamad Niizar (Construction Research Institute of Malaysia (CREAM), 2018)
In geotechnical earthquake engineering problems, dynamic soil properties determination is a critical task. Shear wave velocity (Vs), and shear modulus (G) are fragments of dynamic soil properties. This study focused on the peat shear wave velocity determination using 1-D multichannel analysis of surface waves, the in-situ density using the peat sampler and the shear modulus estimation using empirical formula. The study was conducted at Parit Nipah, Johore and Penor, Pahang as it contains a large composition of peat. The result of the study indicates that, the peat shear wave velocity ranged from 30.4 m/s to 43.8 m/s for Parit Nipah and 43.4 m/s to 105.8 m/s for Penor. While the peat density ranged from 1.00 g/cm³ to 1.24 g/cm³ for Parit Nipah and 0.72 to 1.36 g/cm³ for Penor. The peat shear modulus, Gmax for Parit Nipah ranged from 736.0 kPa to 2589.6 kPa and 1474.7 kPa to 11265.0 kPa for Penor. The results indicate that the peat shear wave velocity was affected by the changes in peat soil density, while the peat density was governed by the depth. The peat shear modulus value was directly proportional to the peat shear wave velocity. Finally, the slight variation in results obtained might be due to the heterogeneity of peat.